Pengaruh Persepsi Risiko dan Kepercayaan pada Vendor terhadap Minat Beli yang Dimediasi oleh Sikap Konsumen Toko Online Lazada di Kota Padang - Fery Ansyah; Abror Abror (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose - This study analyzes: (1) The effect of consumer attitude on purchase intention, (2) The effect of perceived risk on consumer attitude, (3) The effect of perceived risk on purchase intention, (4) The effect of trust in online vendor on consumer attitude, (5) The effect of trust in online vendor on purchase intention.Methodology - This type of research is causative research. The population in this study is customers of Lazada in Padang city. By using purposive sampling we use 200 customers as the respondent. This study used online and offline questionnaires as the data collection instrument, This study analyzed the data by using structural equation modelling (SEM) with smart PLS 3.0 as the software package.Finding - The results of this study indicate that: (1) consumer attitude has a significant effect on purchase intention (2) Perceived risk has a significant effect on consumer attitude (3) Perceived risk has a significant effect on purchase intention, (4) Trust in online vendor has a significant effect on consumer attitude, (5) Trust in online vendor has a significant effect on purchase intention. Keywords: Perceived Risk, Trust in Online Vendor, Consumer Attitude, Purchase Intention